Reaganized Rock: The 1983 Beach Boys Ban and the U.S. Culture Wars - Kolehmainen Pekka M. (Taylor & Francis, 2022)
In 1983, Ronald Reagan’s Interior Secretary, James Watt, decided that rock bands would not perform at the Independence Day celebration that year because they would “attract unwanted elements.” With the Beach Boys having played the event in the past, Watt suffered a backlash even from Reagan himself. In this article, I analyze the media discussions on the ideological undercurrents of how rock was defined as an idea by different people involved. I track rock’s transformation from being a target of a culture war, to the terrain for such a struggle, and finally to a tool for demonstrating ideological allegiances.